STATISTICAL ANALYSIS OF AIR POLLUTION WITH SPECIFIC REGARD TO FACTOR ANALYSIS IN THE CIUC BASIN, ROMANIA - KERESZTES, Réka; RÁPÓ, Eszter (Studia Universitatis Babeș-Bolyai Chemia, 2017)
In the present study, the changes of the concentration of air pollutants were examined, based on air pollution, meteorological and climatologic data gathered over an interval of two years (2012-2013) by the regional measuring station located in the basin, as well as the sources of the air pollutants were studied with the help of factor analysis. Biomass burning, traffic and photochemistry were characteristic regarding the source of air pollutants. This was also confirmed by the correlations between pollutants. Furthermore, the increasingly busy car traffic in the cold season and the atmospheric stability characteristic for it are also important observations with regard to the sources of air pollutants.